KAJIAN PENGENDALIAN PENYAKIT KARAT PADA KEDELAI DENGAN PESTISIDA NABATI - Heriyanto, Heriyanto (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
The study aims to determine the type of botanical pesticides are effective for controlling rust disease on soybean. The research was conducted in the village of Banguntapan, Bantul in June and October 2014. The study used a complete randomized block design with 5 treatments and 4 replication, control materials used are clove oil, lemongrass oil, betel oil, jatropha seed oil and water (control). Applied control rust disease by spraying the leaves of soybean plant age begins at 14 days with an interval of 7 days. The results showed that clove oil is more effective for controlling rust disease than lemongrass oil, betel oil and jatropha seed oil based on the incubation period, the percentage of diseased leaf, the intensity of the attack and the loss amounted to 46.38 percent attack.